Extensive congenital epulis in a newborn: diagnosis and treatment of a rare lesion - Deus, Ciro Borges Duailibe de (2021)
Congenital epulis is a rare benign tumor that affects the oral mucosa of newborns. Despite being benign, this lesion can reach an extensive dimension and impair the function of the maxillomandibular complex for both feeding and breathing, and should therefore be diagnosed as early as possible to perform its excision. This article aims to report a case of diagnosis and treatment of a newborn with large congenital epulis. Patient M.C.A., leucoderma, 2.7 kg, female and normorreative, presented in the physical examination of the immediate postnatal period, a nodular, smooth, non-ulcerated and pediculated lesion with 40 millimeters in its largest diameter, located in the buccal alveolar mucosa of right jaw. With the multiprofessional integration between the pediatric, radiological and buccomaxillofacial medical team, computed tomography and doppler ultrasonography exams were requested and evaluated to assess the blood flow of the lesion and definitive exclusion of the differential diagnosis of hemangioma. The excision procedure was performed under general anesthesia, when the patient was eleven days old, uneventful and the anatomical specimen was stored for histopathological and immunohistochemical evaluation, which confirmed the clinical diagnosis of congenital epulis. The patient showed immediate nutritional recovery and progressed satisfactorily. The congenital epulis, being a rare condition, ends up being underdiagnosed and confused with vascular lesions, therefore, the multiprofessional approach directs the diagnosis and treatment in an appropriate way.